Splenic infarction complicated with abscess after pelvic trauma as the first presentation of patent foramen ovale - A case report. (June 2021) - Demma, J.; Weiss, D.; Kedar, A.; Shussman, N.; Zamir, G.; Pikarsky, A.; Bala, M.
Abstract: Hypercoagulability after trauma is a known entity. Following significant trauma, most guidelines advise anticoagulation treatment for venous thromboembolism (VTE) prophylaxis. VTE following minor trauma convoyed with arterial or systemic embolization dictate the need to search for uncommon source of thromboembolic complications. This is a report of an unusual case of pulmonary and systemic emboli complicated by splenic abscess following minor trauma in a patient with Diabetes Mellitus as the first presentation of patent foramen ovale (PFO).